Clostridium butyricum Supplement Can Ameliorate the Intestinal Barrier Roles in Broiler Chickens Experimentally Infected With Clostridium perfringens - Xu, Xiao; Yang, Shunli; Olajide, Joshua Seun; Qu, Zigang; Gong, Zhenxing; Wang, Jing; Zhang, Yanbing; Wang, Heng; Xiong, Ling; Zhang, Kun; Zhou, Enmin; Cai, Jianping (Frontiers in Physiology, 2021)
Necrotic enteritis (NE), caused by Clostridium perfringens, is an economically important disease in the broiler. Among normal flora in the broiler intestinal region, Clostridium butyricum has been identified as a probiotic agent that reduces the susceptibility of broilers to C. perfringens. However, the effects of C. butyricum supplement on broiler intestinal integrity during NE are largely unknown. In this study, we investigated the effects of C. butyricum on the growth performance, intestinal morphology and barrier function, and the functions of immune-related cytokines under NE in broilers. Chickens were divided into five groups: control group (NC), supplement C. butyricum only group (CB), NE-infected group (PC), supplement C. butyricum from Day 14 (NECB1) to Day 22 NE-infected group, and supplement C. butyricum from Day 1 (NECB2) to Day 22 NE-infected group. The results showed that there were significantly decreased average daily weight gain and increased feed conversion rate in the infected group (PC) compared with the C. butyricum-supplemented groups (NECB1 and NECB2) through the diet. Histopathological observation on the Hematoxylin–Eosin staining avian small intestine sections revealed that supplementation of C. butyricum (NECB1 and NECB2) could increase the intestinal villus height/crypt depth and lessen the intestinal damage under NE. ELISA and Limulus test showed that broilers infected with NE (PC) had higher serum IgA and lipopolysaccharide content; however, after C. butyricum supplementation (NECB1 and NECB2), they returned to a normal level. Furthermore, real-time PCR and Western blot results indicated that compared with PC, supplementing C. butyricum (NECB1 and NECB2) could initialize the expressions of genes related to the intestinal barrier-associated molecules (such as CLDN-1, CLDN-3, OCLN, MUC2, ZO-1, and CLDN5), cytokines (such as IL-10, IL-6, and TGFB1), and C. perfringens plc gene expression. Moreover, the results detected by the Ussing chamber suggested that C. butyricum (NECB1 and NECB2) could amend the decrease in conductivity value and short-circuit current value caused by NE. In addition, NECB2 significantly reduced the upregulation of fluorescein isothiocyanate–dextran flux caused by the NE disease. In conclusion, these findings suggest that dietary supplementation of C. butyricum in broilers with NE improved chicken growth performance, intestinal integrity and barrier function, and immunological status. Notably, no statistical difference was observed with the addition of C. butyricum on day 1 or day 14.